ANALISIS KEBIJAKAN PEMERINTAH TERHADAP PEKERJA MIGRAN INDONESIA DI MASA PANDEMI COVID-19 (Studi Kasus Pemberangkatan PMI di Masa Pandemi) - Ajeng Tiara Bangga Rahmawati (Journal of International Relations Diponegoro, 2023)
Reopening of migrant workers' departures during the covid pandemic presents a contrast to the various protection policies that have been made before. This research aims to answer the research question: "why is the Indonesian government issuing a PMI departure policy during the Covid-19 pandemic?". To answer the formulation of the problem, the theory used is to combine rational actors with policy formulations. This research is explanatory using the content analysis method. This study uses the framework of rational actor by Graham Allison and Philip Zelikow as well as Jonathan Bendor and Thomas H. Hammond was used to find out how much influence the rational thinking style of a policymaker has when a policy is formed. The formation of a new policy by the government regarding the redeployment of PMI during a pandemic is considered a rational policy.Keywords: Indonesian migrant workers', rational actor, policy formulation, foreign exchange, economy